CAGE14-4 Cruise Report: CAGE-CO2 Cruise and GEO3144 Teaching Cruise to the western Svalbard margin and the Barents Sea - Rasmussen, Tine L.; Nielsen, Tove; Zamelczyk, Katarzyna; Sztybor, Kamila (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the afternoon of July 21st to the morning of July 29th 2014, CAGE at the Department of Geology Uit, the Arctic University of Norway, arranged a scientific cruise with teaching (GEO3144/8144- Arctic Marine Geology and Geophysics Cruise) aimed at investigating and teaching students about the western Svalbard margin, methane seep sites at Vestnesa and Storfjorden Trough and the Barents Sea on R/V “Helmer Hanssen”. Investigated areas were (in order of visiting sites on the cruise): Vestnesa Ridge, the west Svalbard slope, Storfjorden Trough, Storfjorden and western Barents Sea. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE – Centre for Arctic Gas hydrate Environment and Climate”, in which the sub-projects “Paleo-CIRCUS”, “OA-Ocean Acidification” is included. A total of 11 gravity cores, 7 box-cores (with a total of 18 sub-samples retrieved), 9 plankton net casts and 16 CTD (conductivity-temperature-depth) casts were performed at Vestnesa Ridge, Storfjorden Fan, Storfjorden Trough, Storfjorden and the western Barents Sea, respectively. All gravity cores were logged onboard by magnetic susceptibility loop sensor for stratigraphical purposes and educational purposes. Chirp profiles and multibeam echo sounder lines were acquired during transits and during surveys of Storfjorden and several pockmarks at the Vestnesa Ridge. A total of 129 lines were collected during transits and during surveys. A total of six seismic lines were performed with the airgun. The cruise may be known as: CAGE14_4_CO2_GEO